Effects of mixed inoculation of Leuconostoc citreum and Lactobacillus plantarum on suansun (Sour bamboo shoot) fermentation. (June 2022) - Lu, Honghao; Huang, Cuiji; Yu, Kena; Liu, Zhaoming
Abstract: To study the effects of mixed starter consisted of different fermentative type of lactic acid bacteria (LAB) on the fermentation of suansun, two lactic acid bacteria ( Leuconostoc citreum NM-12 and Lactobacillus plantarum L 01 ) isolated from Chinese traditional fermented vegetable were used in the preparation of suansun . The fermentation was carried out at ambient temperature (around 25 °C）for 96 h by inoculating different mixing ratios of LAB (inoculated fermentation) or using natural microbes (natural fermentation). The changes of pH, titratable acid (TA), microbe communities, free sugars, organic acids, nitrite and volatile compounds during fermentation were evaluated. Suansun treated with high Leuconostoc citreum ratio inoculation exhibited a quickly change in pH and TA, resulting from the rapid increase in the number of viable cells, at the early stage of fermentation and produced more mannitol (0.12–0.46 mg/mL) and acetic acid (0.93–3.56 mg/mL). However, Suansun treated with high Lactobacillus plantarum ratio inoculation had lower pH and higher TA at the later stage of fermentation and produced more lactic acid (5.32–7.68 mg/mL). No mannitol was detected in suansun when only Lactobacillus plantarum was inoculated in fermentation. No p-cresol was produced in the inoculated fermentation with mixed starter culture, in addition to the production of ethyl acetate and 2.3-butanedione, which had a positive effect on the flavor of suansun . In summary, this study demonstrated the application value of mixed starter consisted of different fermentative type of LAB. LAB types and mixing ratios greatly affected the types and concentration of metabolites in suansun fermentation.